Famine threatens DR Congo - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Democratic Republic of Congo is facing serious food shortages as a result of years of civil war in the country. Yields of cassava, a staple food for 70% of the population, are particularly affected and its deterioration seriously affects the...